Bob - Pearson, Tracey Campbell; Raising Readers Collection (New York : Farrar, Straus, Giroux, 2002)
While looking for someone to teach him how to crow, a rooster learns to sound like many different animals and finds that his new skills come in handy.
560
Accelerated Reader AR
Keywords: Roosters -- Fiction; Animal sounds -- Fiction; Animals -- Fiction; Humorous stories